Pengaruh Air Rebusan Daun Salam Terhadap Pasien Penderita Hipertensi - Yusipa, Rica; Yustiani, Revita; Hartono, Rudi; Siti Risma, N; Fauziah, Sifa (Fakultas Kesehatan Universitas Muhammadiyah Sukabumi, 2022)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and 90mmHg diastolic. Hypertension is often referred to as the